Turn it and turn it again: the vital contribution of Krister Stendahl to Jewish-Christian relations - Boys, Mary C. (Journal of ecumenical studies, 2016)
This essay explores the contributions of the late Lutheran bishop and New Testament scholar, Krister Stendahl, to the church’s rethinking of problematic readings of its sacred texts, particularly with regard to women and Judaism. Stendahl’s pastoral sensitivities gave rise to four phrases that serve as widely accessible hermeneutical “principles”: (1) “It’s not about me.” (2) “Words that grow legs and walk out of their context.” (3) “Christianity as a construct.” (4) “Leave room for holy envy.” Stendahl’s way of articulating brilliant exegetical insights in simple terminology reveals how someone who wrote relatively little made an enormous impact on both biblical scholarship and the church.